VERBAL REPRESENTATION OF HOSPITALITY IN ENGLISH AND UZBEK LINGUISTIC CULTURE (ILMIY TADQIQOTLAR VA YANGI OLAM, 2025)
Hospitality is one of the most significant universal cultural values, yet its verbal representation varies substantially across languages due to differences in social norms, communicative expectations, and cultural worldviews. This study explores the verbal manifestation of hospitality in English and Uzbek linguistic cultures, highlighting similarities and divergences in greeting formulas, invitation patterns, politeness strategies, and culturally marked lexical units. By employing a comparative linguocultural and pragmatic analysis, the research identifies verbal markers that demonstrate how each culture conceptualizes respect, warmth, and social harmony. The findings contribute to a deeper understanding of intercultural communication and suggest methods for improving cross-cultural competence for learners of both English and Uzbek.